Carp Farming in Village Ponds The untapped potential in Tiruvallur District - An overview - Devi, M. Nirmala; Ramasubramanian, G. V. (Indian Farming, 2015)
The Front Line Demonstration on Carp farming showed that composite fish culture is a wonderful avenue for increasing the fish production in Tiruvallur district. The income generated was multifold compared to the expenditure. The demonstration showed that the locally available water bodies in villages and small hamlets can be utilized efficiently. The field day conducted on the day of harvest motivated the other farmers and rural youth of the near by villages to tap the untapped potential of water resources of their habitat. In a nut shell, Composite fish culture is a source for additional income generation by utilizing the unutilized and underutilized aquatic resources. The farmers can also have Integrated Farming System in which fish culture is one of the components in a small area of their holdings. They can rear fish in field channels and paddy fields which would facilitate them to get additional income from diversified sources.